1983
DOI: 10.3109/08860228309076047
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy Associated with the use of Cephalosporin or Moxalactam Antibiotics in Acute and Chronic Renal Failure

Abstract: Nine azotemic patients who developed a coagulopathy associated with the use of either cephalosporin or moxalactam antibiotics are reported. The acute renal failure patients had neoplastic disorders and were considered to be septic at the time that multiple antibiotics were administered. Four of 5 chronic hemo- or peritoneal dialysis patients also received multiple antibiotics. Nevertheless, the coagulopathy seemed to be most closely associated with the administration of the cephalosporin. One patient received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Total osteocalcin was reduced as was carboxylated osteocalcin and thus, the percentage of carboxylation was decreased. In patients with ARF, deficiencies of vitamin K have only been reported during the use of certain cephalosporin antibiotics [28]. In patients on regular hemodialysis therapy it was shown that the vitamin K status is correlated with bone health with vitamin K deficiency present in patients with previous bone fractures [29].…”
Section: Discussionmentioning
confidence: 99%
“…Total osteocalcin was reduced as was carboxylated osteocalcin and thus, the percentage of carboxylation was decreased. In patients with ARF, deficiencies of vitamin K have only been reported during the use of certain cephalosporin antibiotics [28]. In patients on regular hemodialysis therapy it was shown that the vitamin K status is correlated with bone health with vitamin K deficiency present in patients with previous bone fractures [29].…”
Section: Discussionmentioning
confidence: 99%
“…ylation of glutamate residues in clotting factors by MTT, a sulfhydryl leaving group present in the structures of the cephalosporin antibiotics most often associated with hypoprothrombinemia (Black et al, 1983;Lipsky, 1983Lipsky, , 1984Lipsky et al, 1984). Although the structure of cefazolin also includes a potential sulfhydryl leaving group, MTD, and although MTD is also a potent in vitro inhibitor of the ␥-carboxylation of glutamate (Kerremans et al, 1985), hypoprothrombinemia is an unusual complication of cefazolin therapy (Lerner and Lubin, 1974;Clark et al, 1983;Dupuis et al, 1984). In addition, even though MTT can be easily detected in the tissues of subjects treated with cephalosporins which contain that structure (Black et al, 1983), MTD has not been reported to be present in human tissues after cefazolin exposure.…”
Section: Fig 3 Hplc Of the Methylated Product Generated With Heatedmentioning
confidence: 99%
“…If MTD, like MTT, is a leaving group that is released in human tissues, and if MTD is, as previously reported, more potent than MTT as an inhibitor of the ␥-carboxylation of glutamate (Kerremans et al, 1985), why does hypoprothrombinemia occur so much less frequently after exposure to cefazolin than after exposure to cephalosporins that include MTT in their structures. It should be noted that cefazolin administration has been associated with hypoprothrombinemia, not only in patients (Lerner and Lubin, 1974;Clark et al, 1983;Dupuis et al, 1984) but also in vitamin K depleted rats (Lipsky FIG. 6…”
Section: Fig 3 Hplc Of the Methylated Product Generated With Heatedmentioning
confidence: 99%
See 1 more Smart Citation